2012
DOI: 10.1002/mabi.201100404
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethyleneimine)‐Mediated Large‐Scale Transient Gene Expression: Influence of Molecular Weight, Polydispersity and N‐Propionyl Groups

Abstract: Three synthesis lots of linear poly(ethyleneimine) (PEI) are compared to a fully hydrolyzed linear PEI (commercially available as PEI "Max") regarding structure, polyplex formation with plasmid DNA, and transfection of suspension-adapted HEK-293E cells. PEI "Max" binds DNA more efficiently than the other PEIs, but it is the least effective in terms of transient recombinant protein yield. One PEI lot is fractionated by means of SEC. The fractions of high-M(n) PEI are the most efficient for complex formation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
1
20
0
1
Order By: Relevance
“…15 kDa. (Falco et al, 2009;Kadlecova et al, 2012) However, neither group performed an LDH or similar assay to assess the effect of the molecular weight on cell membrane disruption. Boe et al assayed a limited range of commercial PEI samples of both linear and branched structures on osteosarcoma cells, with mitochondrial activity measured by (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) (MTS) after 24 h exposure.…”
Section: Introductionmentioning
confidence: 99%
“…15 kDa. (Falco et al, 2009;Kadlecova et al, 2012) However, neither group performed an LDH or similar assay to assess the effect of the molecular weight on cell membrane disruption. Boe et al assayed a limited range of commercial PEI samples of both linear and branched structures on osteosarcoma cells, with mitochondrial activity measured by (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) (MTS) after 24 h exposure.…”
Section: Introductionmentioning
confidence: 99%
“…PDMAEMA, a dual‐responsive polymer (temperature and pH), has been widely used in the gene delivery area since its first use as a gene transfection system in 1996 by Cherng et al Since then, several studies were performed to evaluate different aspects on the transfection efficiency of this polymer, such as, the role of molecular weight, polyplex size, and transfection parameters as pH, ionic strength, temperature, viscosity, polymer/plasmid (N/P) ratio and the presence of stabilizers . Among these, the molecular weight has been considered as one of the most important aspects on the transfection activity . It has been reported that PDMAEMA with higher molecular weight leads to smaller polyplexes that are more efficient in transfection.…”
Section: Introductionmentioning
confidence: 99%
“…The solution is filter sterilized and stored at À20°C. Linear 25 kDa PEI in this form usually has a number-average molecular weight (M n ) of 6-7 kg/mol with the range being 2-26 kg/mol [88]. Its polydispersity index (PDI) is about 1.9, an important property for efficient DNA delivery in HEK-293E cells [88].…”
Section: Polyethyleneiminementioning
confidence: 99%
“…Linear 25 kDa PEI in this form usually has a number-average molecular weight (M n ) of 6-7 kg/mol with the range being 2-26 kg/mol [88]. Its polydispersity index (PDI) is about 1.9, an important property for efficient DNA delivery in HEK-293E cells [88]. In the synthesis of PEI from 2ethyloxazoline, there is an acidification step to remove N-propionyl groups from the amine.…”
Section: Polyethyleneiminementioning
confidence: 99%
See 1 more Smart Citation